Investigating and evaluating some of the characteristics of severity of climatic droughts in Kerman and Shiraz meteorological stations - Mohammad Hossein Mobin; Zahra Zarei; Hamid Sodayizadeh (مخاطرات محیط طبیعی, 2019)
Among the climatic phenomena that affect communities and the environment, climatic drought is one of the most complex ones. The purpose of this research is to express some of the characteristics of climate drought, especially their severity in arid and semi-arid regions of Iran. After providing hourly data on average, maximum and minimum temperature as well as average rainfall, of Kerman and Shiraz synoptic stations which are representative of arid and semi-arid regions of the country respectively, and converting them into daily and monthly scales, the severity of climate droughts was calculated based on four SPI, RDI, SPEI and EDI indicators during the statistical period of 1965-2015 and at 5 different time steps. The efficiency of each indicator was evaluated in determining the characteristics of climate drought. The results showed that the drought severity estimated by each of the indices at different time steps in Kerman and Shiraz has the same monthly changes and fluctuations. But in each region, based on the type of climate, the index that has the highest correlation with the others at different time steps is different. So, in Kerman, RDI6 (R2=0.64) and RDI9 (R2=0.70) in Shiraz had the highest correlation (higher coefficient of determination) with other indices, and have higher efficiency for Justifying the quantitative changes of other indices. In addition, at different time steps, the SPEI in Kerman and RDI in Shiraz have good performance in determining the number of dry months. Meanwhile, in terms of the frequency of occurrence of dry months in different drought severities, the class of mild dryness (0> I> -1) with a frequency of 65% and then the moderate dryness class (1> I> -1.5) had the highest percentage Frequency, and severe dry and severe drought (I>1.5) had the lowest percentage of abundance (15%) at both stations.